IMPLEMENTASI KURIKULUM BERBASIS CINTA (KBC) DALAM PEMBELAJARAN AKIDAH AKHLAK DI MI NU WALISONGO SUMBERREJO - Zakiyatur Rofiah, Firda; Intan Nuraini, Dea (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Love-Based Curriculum (Kurikulum Berbasis Cinta/KBC) is a madrasah curriculum policy launched by the Indonesian Ministry of Religious Affairs through Ministerial Decree Number 1503 of 2025, positioning love as the central axis for shaping students' character across all levels of madrasah education, including Islamic Elementary Schools (MI). This article aims to describe the planning, implementation, and evaluation of KBC in Akidah Akhlak (Islamic Faith and Ethics) instruction at MI NU Walisongo Sumberrejo, as well as to identify its supporting and inhibiting factors. A descriptive qualitative approach was employed, with data collected through classroom observation, interviews with teachers and the head of the madrasah, and documentation of teaching materials. The findings indicate that KBC implementation is carried out by internalizing five pillars of love—love for God, self, others, knowledge, and the environment/homeland—into lesson planning, humanistic and student-centered instruction, and holistic assessment covering attitudes, knowledge, and skills. This implementation has fostered stronger emotional bonds between teachers and students, greater mutual respect, and a warmer, more enjoyable classroom atmosphere. Challenges identified include teachers' partial understanding of the KBC concept, limited instructional time, and insufficient facilities for project-based learning. This article recommends strengthening teacher training, providing technical guidelines, and enhancing collaboration with parents to optimize KBC implementation.